Event-based Controller Design for Networked Control Systems with Time-varying Random Delays - Beheshte Sadeghi Sabzevari; Mohammad Haddad Zarif; Seyed Kamal Hosseini Sani (Majlesi Journal of Electrical Engineering)
This paper is concerned with a controller design method for Networked Control Systems (NCSs) with time-varying random delays. The proposed controller is an event-based controller and is able to effectively save the network bandwidth and energy resources of the system in comparison with common control schemes while guaranteeing the stability of the system. The proposed controller switches between two main triggering schemes: event-triggered control scheme and self-triggered control scheme. The stability issue in this combinatorial method is also considered. The validity of the proposed algorithm is confirmed via simulation results and the results are well compared with results from exerting event-triggered and self-triggered control individually.